Reviewing Lessons With Mind Mapping By The Help of 6 Questions Cognitive Model To Help Students Learn Better - Xinxin Li; Ying Zhou; Jihe Chen; Zhengang Li (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
Review lessons after class can help students increase student achievement but not necessarily students know how to review effective and efficient learning. This learning goal is to explain how to review effective and efficient lessons using Mind Mapping and 6 Cognitive Model Questions. The subject on this study is a junior high school student. The topic of Linear Mathematics Equations in Two variables is described using a qualitative tendency. Study shows that Mind Mapping and 6 Cognitive Model Questions can improve critical thinking skills, high order thinking abilities and systematic thinking skills. Mind Mapping and 6 Cognitive Models Helping Students to review Linear Equations in Two Variables and get Deep Learning.